Queijo Prato com teor reduzido de gordura adicionado de enzima proteolítica: características físicas e sensoriais - Garcia, Graziele Aparecida Chiuchi [UNESP]; Penna, Ana Lúcia Barretto [UNESP] (My University, 2010)
The Prato cheese is the second most consumed cheese in Brazil. It is produced by milk enzymatic coagulation, and maturated for at least 25 days; it is classified as fatty cheese and of medium moisture. Due to the concern to health, the cheeses consumers have been seeking for products with low fat contents; however fat is essential for providing desirable sensory and physiologic characteristics, such as flavor, softness and texture to cheeses. Alterations on the technological processing of low fat cheeses have been made seeking for improved products, and the use of proteolytic enzymes has been a significant strategy. The meltability, color and sensory characteristics are fundamental quality indicators of the final products. This study reports the findings from the analyses on the physical and sensory characteristics of low fat Prato cheese with addition of proteolytic enzyme – fastuosain, that is extracted from unripe gravata fruit. The addition of fastuosain improved the quality of the product, as this additive neither affected the meltability, nor produced bitterness, which is a common unpleasant taste in low fat cheeses.

O queijo Prato, segundo queijo mais consumido no Brasil, obtido por coagulação enzimática do leite e maturado por pelo menos 25 dias, é classificado como gordo e de média umidade. Devido à preocupação com a saúde, os consumidores de queijos têm procurado produtos em suas versões com menor teor de gordura. Contudo, a gordura confere as características sensoriais desejáveis, como sabor, cremosidade, maciez e textura aos queijos. Alterações têm sido introduzidas no processo tecnológico de fabricação dos queijos com teor reduzido de gordura, com o intuito de efetuar melhoria nesses produtos; e o uso de enzimas proteolíticas é uma importante estratégia a ser considerada. A capacidade de derretimento, cor e avaliação sensorial são fundamentais indicadores da qualidade dos produtos obtidos. O presente trabalho analisou as características físicas e sensoriais de queijo Prato com teor reduzido de gordura adicionadoda enzima proteolítica fastuosaína, extraída do fruto verde do gravatá. A adição da fastuosaína não interferiu na capacidade de derretimento, tampouco promoveu o desenvolvimento de amargor, que é característica comum não apreciada em queijos com teor reduzido de gordura.
Reduced fat Prato cheese added of proteolytic enzyme: physical and sensorial characteristics
Keywords: queijo Prato; enzima proteolítica; capacidade de derretimento; cor; avaliação sensorial; modelo Etana; Prato cheese; proteolytic enzyme; meltability; color; sensory evaluation; Etana model